Stock Optimization To Face The Level of Personal Protective Equipment Replacement in The General Affairs Division Using The Wecare System at PT Astra Daihatsu Motor - Okin Ringan Purba; Johanes Kurniawan Liauw; Basri Fahriza; Alicia Putri Sandyta (Dinasti Publisher, 2026)
The current issue faced by PT Astra Daihatsu Motor is the high rate of Personal Protective Equipment (PPE) replacement, which is caused by various contributing factors. This study aims to examine and analyze the effects of workload, number of workers, procurement forecasting, and the “WeCare” one-system service on the optimization of PPE procurement stock at PT Astra Daihatsu Motor, as well as to generate procurement forecasting calculations for PPE for the year 2025. This research employs a mixed-methods approach, combining qualitative and quantitative methods. Observations were conducted to examine existing phenomena related to PPE replacement. Furthermore, the research population consists of employees from the three divisions with the largest workforce located at the Karawang Assembly Plant of PT Astra Daihatsu Motor. A total of 591 respondents were selected as the research sample from a population of 2,499 employees. The results of the study indicate an R-square value of 46.1%, which means that workload, number of workers, procurement forecasting, and the “WeCare” one-system service collectively contribute 46.1% to the optimization of PPE procurement stock, while the remaining 53.9% is influenced by other factors. Procurement forecasting related to PPE replacement was also carried out using the Holt–Winters method to optimize PPE procurement for the year 2025. Based on the findings of this study, it is expected that management can conduct evaluations of PPE procurement, particularly to improve the optimization of PPE procurement stock.